Productive restructuring, State reform and educational policies in post 1990 Brazil - Wanessa Cardoso Gomes Muniz; Roberto Francisco de Carvalho; Núbia Mária Soares de Souza (Universidade Federal do Norte do Tocantins, 2023)
The article aims to analyze the Brazilian educational policies of the nineties. Therefore, the international political-economic scenario of Latin America in the late seventies and eighties is presented. It is intended to identify, in the same way, trends and constitutive concepts of educational policies, especially the particular use that is made of the notion of "competences", based on documents from national organizations and multilateral agencies. To support the choices and discussions developed in the article, historical-dialectical materialism is used, as it makes it possible to historically analyze the changes in educational legislation. The results reveal that the educational policies of that period were based on the perspective of capital, following the orientation of international organizations, of a neoliberal nature.